Structure of the human multidrug transporter ABCG2 - Taylor, Nicholas M. I.; Manolaridis, Ioannis; Jackson, Scott M.; Kowal, Julia; Stahlberg, Henning; Locher, Kaspar P. (Nature (London), 2017)
ABCG2 is a constitutively expressed ATP-binding cassette (ABC) transporter that protects many tissues against xenobiotic molecules. Its activity affects the pharmacokinetics of commonly used drugs and limits the delivery of therapeutics into tumour cells, thus contributing to multidrug resistance. Here we present the structure of human ABCG2 determined by cryo-electron microscopy, providing the first high-resolution insight into a human multidrug transporter. We visualize ABCG2 in complex with two antigen-binding fragments of the human-specific, inhibitory antibody 5D3 that recognizes extracellular loops of the transporter. We observe two cholesterol molecules bound in the multidrug-binding pocket that is located in a central, hydrophobic, inward-facing translocation pathway between the transmembrane domains. Combined with functional in vitro analyses, our results suggest a multidrug recognition and transport mechanism of ABCG2, rationalize disease-causing single nucleotide polymorphisms and the allosteric inhibition by the 5D3 antibody, and provide the structural basis of cholesterol recognition by other G-subfamily ABC transporters. The structure of human ABCG2 bound to an inhibitory antibody using cryo-electron microscopy, representing the first high-resolution structural data of a human multidrug transporter. Structure of a human multi-drug transporter ABCG2 is an ATP-binding cassette (ABC) transporter sometimes referred to as the breast cancer resistance protein. It is a multi-drug transporter that protects many tissues from foreign molecules and as such it has a key role in the effectiveness of commonly used oral drugs. It is also important in cancer treatments for the potential exploitation of the delivery of therapeutics to tumour cells. Here the authors present the structure of human ABCG2 bound to an inhibitory antibody, obtained using cryo-electron microscopy. This represents the first high-resolution structural data of a human multi-drug transporter. Two cholesterol molecules are bound to the multidrug binding pocket between the transmembrane domains, providing key information on substrate recognition by other ABC transporters.